(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2023)
Recently, there are three significant periods, which changed the world in almost all aspects – health, economy, education, travel and tourism, way of working, global cooperation, global energy crisis etc. Based on that, this paper analyses the top selling product in a company for each period, and presents their selling trend. The analysis was performed on a dataset from a company selling print services and products, using the concept of Business Intelligence, i.e. the powerful combination of Data Warehouse, ETL process and PowerBI. The results of the research confirmed that the announced periods made a significant impact on the world, businesses, and customer behavior. On the other side, the tools that we used in the research proved to be effective in transforming data and analyzing customer behavior.